Treatment of renal leiomyosarcoma with right atrial tumor embolus without cardiopulmonary bypass: a case report - Duan, Yuanpeng; Bi, Chengwei; Zhang, Guoying; Xing, Yapeng; Qin, Yang; Zhao, Bin (Frontiers in Oncology, 2024)
Objective To investigate the clinical manifestations, imaging and pathological features, treatment methods and prognosis of primary leiomyosarcoma of kidney, and the choice of treatment with tumor thrombus.Methods The clinical data of a patient with primary renal leiomyosarcoma complicated with inferior vena cava and right atrial tumor thrombus were retrospectively analyzed. Radical resection of right kidney without cardiopulmonary bypass and removal of inferior vena cava and right atrial tumor thrombus were performed. Adjuvant intravenous chemotherapy was given according to the results, and follow-up observation was made.Results Postoperative pathological findings were: leiomyosarcoma (right renal tumor), the size of the mass was about 12.1 cm, and no cancer was found at the incision end of the right ureter.Conclusion Primary leiomyosarcoma of kidney is rare in clinical practice, and complication of right atrial tumor embolus is even rarer. The disease has high malignant degree and poor prognosis. The clinical manifestations and imaging examinations were non-specific, and pathological diagnosis was the gold standard. Radical surgical resection is the main treatment method at present, and it provides experience for the treatment of grade IV tumor thrombus without cardiopulmonary bypass.